World view foundations of social environmental practices in «good society» - Koval, Ekaterina A. (Journal of the Belarusian State University. Ecology, 2018)
The article is devoted to the analysis of such world view foundations of social ecological practices as anthropocentrism, biocentrism, ecocentrism and transhumanism. At the same time, social ecological practices are considered not in the context of social reality, but in the context of such variant of social imaginary as «good society». The main research method is a comparative analysis that allows one to compare the perspectives of anthropocentrism, biocentrism, ecocentrism and transhumanism as the basis for social ecological practices in the structure of liberal and communitarian models of «good society». The main result of the study is the definition of the most constructive combination of the world view foundations of practices carried out with the aim of preserving the non-anthropic nature and the model of «good society». It is established that anthropocentrism is the optimal basis for social ecological practices in liberal models and for communitarianism models anthropocentrism, biocentrism and ecocentrism. Transhumanism is a world view that is based on the value of overcoming by person of limiting everything, including aging and death. So transhumanism is focused on posthuman for which are likely to be relevant alternative forms of sociality.